1998
DOI: 10.1515/jpem.1998.11.6.719
|View full text |Cite
|
Sign up to set email alerts
|

Serum Thyroid Hormone and Thyroid Gland Weight Measurements in Protein-Energy Malnutrition

Abstract: Protein-energy malnutrition (PEM) is a problem which concerns about half the world's children. We investigated the effects of malnutrition on thyroid gland weight and thyroid hormone levels. 22 children suffering from malnutrition (14 children suffering from marasmus and 8 children suffering from kwashiorkor) and 7 healthy controls were studied. Malnutrition was confirmed clinically and according to the Wellcome classification definition of malnutrition. Serum thyroid hormone concentrations were measured by ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…These authors did not measure other anthropometric parameters of nutrition such as MUAC, TC and TSF. Positive correlation between thyroid weight measured scintigraphically and the ratio of thyroid gland weight to BSA has also been shown (16). The Gujarati children showed the expected positive correlation r 0X12±0X20Y P , 0X05 of thyroid size to variables such as BSA, weight, height and HAZ.…”
Section: Discussionmentioning
confidence: 74%
“…These authors did not measure other anthropometric parameters of nutrition such as MUAC, TC and TSF. Positive correlation between thyroid weight measured scintigraphically and the ratio of thyroid gland weight to BSA has also been shown (16). The Gujarati children showed the expected positive correlation r 0X12±0X20Y P , 0X05 of thyroid size to variables such as BSA, weight, height and HAZ.…”
Section: Discussionmentioning
confidence: 74%
“…Amino acid pool gets decreased to 50% of normal. [11] Protein energy malnutrition is a nutritional deficiency resulting from either inadequate energy (calorie) or protein intake. The spectrum of protein energy malnutrition includes underweight children, kwashiorkor, marasmus, marasmic kwashiorkor.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Similar results are reported by study done by Kumar S et al, Orbak Z et al and study conducted by Das BK et al, found that mean T 3 levels was significantly lower in malnourished children as compared to controls, however in their study they found no significant difference in mean T 4 levels of cases and controls. [19][20][21] Low T 3 levels in children with PEM is probably due to low binding proteins, impaired thyroxine monodeiodination in liver which leads to decreased peripheral conversion of T 4 to T 3 and elevated corticosteroids which is often seen in children with malnutrition (acts by inhibiting 5' deiodinase system) and low T 4 levels in children with PEM can be due to fall in thyroid secretion rate, depletion of reserves and failure of the adaptive mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…17,18,21 In contrast to present study, study conducted by Orbak Z et al, found that mean TSH levels of children with PEM were higher as compared to controls, study conducted by Kumar S et al, found that mean TSH levels showed a positive increase with increase in severity of PEM with maximum increase been observed in grade III PEM (One-way ANOVA; p= 0.015). 19,20 Normal TSH levels in children with PEM is possibly due to T 4 undergoing intracellular monodeiodination to form T 3 at pituitary level causing negative feedback inhibition of secretion of TSH, central unresponsiveness to low T 3 levels due to low intracellular receptor capacity.…”
Section: Discussionmentioning
confidence: 99%